Medieval women and urban justice : commerce, crime and community in England, 1300-1500 - Phipps, Teresa; Manchester University Press (Manchester, UK : Manchester University Press, 2020)
This book provides a detailed analysis of women's involvement in litigation and other legal actions within their local communities in late-medieval England. It draws upon the rich records of three English towns - Nottingham, Chester and Winchester - and their courts to bring to life the experiences of hundreds of women within the systems of local justice. Through comparison of the records of three towns, and of women's roles in different types of legal action, the book reveals the complex ways in which individual women's legal status could vary according to their marital status, different types of plea and the town that they lived inches At this lowest level of medieval law, women's status was malleable, making each woman's experience of justice unique.
"Medieval women and urban justice explores legal actions involving women in three medieval towns - Nottingham, Chester, and Winchester - during the fourteenth and fifteenth centuries. It details women's involvement in litigation concerning debt and trespass, as well as the actions for which they were punished under local policing and regulations.Through the examination of original court records, the book reveals the identities of hundreds of ordinary urban women and the wide range of lawsuits and actions that they participated in. It pays close attention to the experiences of married women and the complex and malleable nature of coverture, which did not always make them legally invisible. The book concentrates on the main ways that women's personal actions drew them into contact with the law: litigation relating to complaints of debt and trespass, the regulation of trade, and the policing of misbehaviour by urban authorities. This allows for consideration and comparison of the differing ways that women's legal status was defined according to various situations and pleas. Throughout, the records of the three towns are compared to highlight the varying experiences of women living in different places and under different legal customs. This book will be of interest to students and scholars of medieval women, urban society, and the law, due to the detail with which it explains the workings of the law in different towns. It also makes a significant contribution to debates on the nature of coverture in the Middle Ages and women's ability to access justice." -- Back cover.
Introduction -- 1. Women, town courts and customary law in context -- 2. Commerce, credit and coverture: women and debt litigation -- 3. Law and the regulation of women's work -- 4. Violence, property and 'bad speech': women and trespass litigation -- 5. Public disorder, policing and misbehaving women -- Conclusion -- Index.
Made available via: manchesterhive.
MUP 2020 titles.
Includes index.
In English.
JSTOR
Keywords: Women -- Law and legislation -- England -- To 1500.; Women -- Social conditions -- Middle Ages; Law, Medieval -- Women; Law, Medieval; England -- Social conditions -- 1066-1485.; Droit médiéval -- Femmes; Droit médiéval.; Angleterre -- Conditions sociales -- 1066-1485.; HISTORY / Europe / Great Britain / Norman Conquest to Late Medieval (1066-1485).; Law, Medieval; Social conditions; Women -- Legal status, laws, etc; Women -- Social conditions; England; Women; Gender identity; Legal status; Gender; To 1500; History